Majalah Sains: Skrining Fitokimia Ekstrak Daun Kulur (Artocarpus Camansi) - Zomratus Solehah; Aliefman Hakim; Jeckson Siahaan (Chemistry Education Practice, 2025)
This study aims to produce a science magazine, analyze the level of validity and the level of practicality of student responses to science magazines on phytochemical screening and antibacterial and antifungal activity tests of kulur (artocarpus camansi) leaf extracts. The sample in this study used purposive sampling technique, namely 30 students who have programmed Natural Material Chemistry courses and are not currently participating in the MBKM program. Data collection methods used in this study are expert validation sheets and student response questionnaire sheets. The data analysis technique used was data analysis of validation results and analysis of student responses. The results of this study indicate that science magazines have been developed and are feasible to use with an average expert validation score of Aiken's V index = 0.94 which is included in the very valid category, besides the results of student response trials show that science magazines get an average percentage of practicality of 92% which is included in the very practical category. Keywords: Science Magazine, Phytochemical Screening, Antibacterial, Antifungal, Kulur Leaf, Validity, Practicality